The Effect of Rehabilitation Program For Hamstring Partial Tear In Advance Soccer Players - Hameed, Ismaeel; Altay, Usama (Journal of Physical Education, 2019)
Soccer is considered one of the sports that famous for its competitive nature during matches that makes players prone to injuries especially in muscles, tendons, ligaments, bones and joints. Hamstring is the most common injury in soccer thus the importance of the research lies in designing a rehabilitation program that consists of therapeutic exercises for hamstring muscles as well as for precaution against future injuries. The problem of the research is that partial tear in soccer players’ hamstring muscles occurs in 6 – 7 players out of 25 in players who suffered previously from the same injury. The researchers used the experimental method on 6 advance soccer players who suffer from partial tear in hamstring. The program was applied for 6 weeks with 3 rehabilitating sessions per week. The results showed the significant effect of the rehabilitation program in healing partial tear in hamstring muscles. The researchers recommended making similar studies on other subjects using other variables.